Materielle Kulturen des Bergbaus | Material Cultures of Mining Zugänge, Aspekte und Beispiele | Approaches, Aspects and Examples - Farrenkopf, Michael / Siemer (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2022)
This volume presents the papers given at an international conference held at the German Mining Museum in Bochum in late 2019, which reflect upon new approaches from material culture studies in relation to mining history, presenting examples of objects on a spectrum ranging from archeology to industrial and economic history, and the history of technology.